Non-neuronal acetylcholinesterase activity shows limited utility for early detection of sepsis - Živković, Aleksandar; Schmidt, Karsten; Hofer, Stefan; Brenner, Thorsten; Weigand, Markus A.; Decker, Sebastian (Biomedicines, 2023)
Sepsis is a severe systemic inflammatory condition characterized by rapid clinical deterioration and organ dysfunction. The cholinergic system has been implicated in modulating the inflammatory response. Acetylcholinesterase (AChE), an enzyme primarily responsible for the hydrolysis of acetylcholine, has been proposed as a potential early indicator of sepsis onset. However, the exact role of non-neuronal AChE activity in sepsis and its correlation with disease severity and patient outcomes remain unclear. This study aimed to investigate the involvement of AChE activity in sepsis and evaluate its association with disease severity and clinical outcomes.
Gesehen am 29.11.2023